The Effect of Work-Life Balance and Organizational Commitment on Turnover Intention with Career Development as a Moderating Variable - Annisa Ramadhan; Hasna Sabrina Septiani Hasna; Canisa Helmi Helmi (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This research aims to obtain empirical evidence about the effect of work life balance and organizational commitment on turnover intention with career development as a moderasi variable Design/methodology/approach – This research uses a quantitative type of research. This research was conducted using a questionnaire distributed to educators in private institutions, namely as many as 35 questionnaires distributed via email and social media. Each questionnaire distributed contains 30 statements for respondents to answer. From the distribution of the questionnaire, 30 respondents provided answers from 2 private institutions. To get the results of this research, researchers used PLS SEM Version 3.0. Findings – The results of this research found that work life balance has a negative and insignificant effect on turnover intention, organizational commitment has a positive and insignificant effect on turnover intention, career development can weaken the relationship between work life balance and turnover intention, career development can strengthen the relationship between organizational commitment to turnover intention. Research limitations/implications – The focus is to explore the relationship between these independent variables and turnover intention, emphasizing the importance of understanding the intention to leave a job among educators in private educational institutions.